Test-retest reliability of gastrocnemius medialis fascicle force-length relationship - Mornas, A.; Hollville, E.; Brocherie, F.; Derouck, T.; Racinais, S.; Guilhem, G. (Journal of Biomechanics, 2024)
Fascicle force-length relationship is one major basic mechanical property of skeletal muscle, subsequently influencing movement mechanics. While force-length properties are increasingly described through ultrafast ultrasound imaging, their test-retest reliability remains unknown. Using ultrafast ultrasound, and electrically evoked contractions at various ankle angles, gastrocnemius medialis fascicle force-length relationship was assessed twice, few days apart, in sixteen participants. The test-retest reliability of the resulting fascicle force-length relationship key parameters — i.e., maximal force (Fmax), and optimal fascicle length (L0) — was evaluated considering (i) all the trials obtained at each ankle joint and (ii) the mean of the two trials obtained at each tested angle. Considering all trials, L0 indicated a `high` test-retest reliability, with intra-class correlation coefficients (ICC) of 0.89 and Fmax a `moderate` reliability (ICC = 0.71), while when averaging the two trials L0 reliability was `very-high` (ICC = 0.91), and Fmax reliability `moderate` (ICC = 0.73). All values of coefficient of variation and standard error of measurement were low, i.e., =7.7 % and =0.35 cm for L0 and =3.4 N for Fmax, respectively. Higher absolute reliability was reported for L0 than Fmax, with better reliability when averaging the two trials at each angle. All these parameters, in accordance with the limit of agreement, demonstrated that L0 and Fmax test-retest reliability is acceptable, particularly when averaging multiple points obtained at a given angle. Interestingly, the shape of the fascicle force-length relationship is more variable. Therefore, L0 and Fmax can be used to compare between days-effects following an intervention, while a comparison of fascicle operating lengths may require more precautions.